Improving VAT collection efficiency through policy design and compliance improvement and moderated by control of corruption - Wijaya, Suparna; Bhuana, Bhima Chandra (WIM Solusi Prima, 2024)
Value Added Tax (VAT) is increasingly relied upon by an increasing number of economies, as shown by the global trend of increasing standard tax rates, but raises questions about the efficiency of its levy. This study revisits the determinants of VAT collection efficiency by using the C-efficiency ratio approach. Using a dataset of countries in the SEAO region (East Asia, Southeast Asia, and the Pacific), this study was performed quantitatively using a panel data regression analysis. The results show that the government effectiveness index is unlikely to be an appropriate proxy for the compliance gap. In terms of the policy gap, policy changes by increasing the standard VAT rate might reduce the C-efficiency ratio, whereas lowering the VAT registration threshold might not improve the C-efficiency ratio. However, the control of corruption index as a moderating variable could antagonize the negative effect of the VAT standard rate on the C-efficiency ratio. This finding corroborates previous studies and encourages discussion to find variables that better measure compliance and policy gap.